Macular thickness evaluation using the optical coherence tomography in normal Indian eyes. - Tewari Hem; Wagh Vijay; Sony Parul; Venkatesh Pradeep; Singh Rajbeer (Indian Journal of Ophthalmology, 2004)
PURPOSE: To determine the normative values for macular thickness and volume by Optical Coherence Tomography (OCT 3) in healthy Indian subjects. METHODS: The macula of 170 consecutive, randomly selected normal subjects was imaged on OCT 3 in this cross-sectional study. OCT parameters of macular thickness were analysed with baseline variables including age, gender, axial length and refractive error. RESULTS: The average foveal thickness in the population under study was 149.16 +/- 21.15 micro. Macular thickness and volume parameters of OCT correlated significantly (Pearson′s Correlation coefficient) with age (r=0.23, P<0.01), but not with gender, axial length and refraction. CONCLUSIONS: The macular thickness and volume parameters have a significant correlation with age. This normative database of macular thickness by OCT in Indian eyes may be a useful guideline for management and further research in diseases of the macula and glaucoma.